Factors affecting the school selection decision of students at Binh Duong University - Tra, Thanh Trúc; Cao , Thị Việt Hương (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
This study focuses on evaluating the factors affecting the decision to choose a school of students at Binh Duong University (BDU). Data collected from 297 first-year students, through statistical analysis with quantitative techniques used for a model consisting of six groups of independent variables: quality of education & training facilities; financial support and procedures; personal factors; social factors; learning environment; chances of admission and graduation; while the dependent variable is the decision to choose a school of students at BDU. The results show that the above factors all affect the decision to choose a school of students (except for the factor of quality of education and training facilities) at the 1% significance level; in which the factor of "financial support and procedures" has the greatest influence. Thereby, the author proposes some implications to improve the decision to choose a school from the students and help the University have a more effective communication and enrollment strategy.